MOTIVASI IBU HAMIL DALAM MENGIKUTI SENAM HAMIL DI POLINDES DESA SIMBARINGIN - Wiwit Sulistyawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
Pregnancy exercise is motion exercise therapy given to pregnant women to prepare themselves, both physically and mentally to face and prepare for a fast, safe and spontaneous delivery. Motivation is a stimulus or encouragement related to generating something Positive motivation can be influenced by the mother having the opportunity to have the means to do pregnancy exercise as well as support from family and closest people who provide encouragement to pregnant women. Knowledge is influenced by education, age and birth spacing as well as experience in pregnant women regarding the understanding of the benefits of pregnant exercise for pregnant women influencing pregnant women to have strong motivation. this type of research is descriptive, the variable used is the motivation of pregnant women who do pregnancy exercise, a sample of 24 respondents, data collection techniques editing, coding, scoring, tabulating. The results showed that more than 50% of respondents had moderate motivation to do pregnancy exercise. 13 pregnant women (54.16%). Health workers or midwives further improve their performance in providing optimal health services by improving quality and comprehensive services, especially in providing counseling by providing leaflets and other media to pregnant women.